Equity short-term finance under Philip II, with an option to long-term funded debt - Carlos Álvarez-Nogal; Christophe Chamley (European Historical Economics Society (EHES), 2015)
Men of finance raised funds for loans, asientos, to Philip II by trading short-term financial instruments in credit markets and by selling long-term annuities, juros. These activities are illustrated by an asiento with the Maluenda brothers (July 13, 1595), where short-term credit secured by the equity of the fleets from the Indies were, for more than one half, converted into funded life annuities that were sold by the Maluendas. The new analysis of this asiento relies on its dossier of more than 400 pages in the archives of Simancas, including the contract, the monitoring attachments, and the final audit.
Keywords: N01; N13; N23; N43; 330; public finances; Philip II; asientos; juros; methodology; archives; verification